Seismic Vulnerability Index Microzonation In Nagari Tanjung Alai, X Koto Singkarak Sub- District, Solok District Using Hvsr Method - Habib Muzafi; Akmam Akmam; Nofi Sudiar; Zulhendra Zulhendra (Department of Physics, Universitas Negeri Padang, 2026)
Nagari Tanjung Alai is located on the fault of the Indo- Australian plate and the Eurasian plate which causes this area to become an earthquake-prone area. An earthquake occurs when the earth trembles or shifts abruptly as a result of tectonic plate movement, causing the rock strata on the earth's surface to shift. Earthquakes in the Nagari Tanjung Alai area can face serious problems, especially earthquakes can threaten public safety, earthquakes can cause damage to infrastructure such as houses and roads, worse earthquakes can trigger the movement of land masses which results in other disasters such as landslides and liquefaction. One method that can be used to identify earthquake- prone areas is the HVSR (Horizontal Vertical Spectral Ratio) method. One technique for analyzing microtremor data is the HVSR approach, which compares the vertical and horizontal components of the microtremor signal. The purpose of this research is to identify and map the microzonation of dominant frequency, amplification factor, and seismic vulnerability index in Nagari Tanjung Alai, X Koto Singkarak District, Solok Regency based on microtremor data processed using the HVSR method. This research is expected to contribute significantly to the understanding of earthquake disaster risk in the area. The HVSR technique of analysis reveals that the major frequency value falls between 0.5 Hz - 8.5 Hz, the amplification value ranges from 1.54 - 7.322, and The value of the seismic vulnerability index falls between 0.63312 to 107.223. Therefore, Nagari Tanjung Alai can be classified as having a high seismic vulnerability index.